2011
DOI: 10.1556/oh.2011.29233
|View full text |Cite
|
Sign up to set email alerts
|

Results of the first human papilloma virus center in Hungary (2007–2011)

Abstract: A humán papillomavírus (HPV) a XXI. század leggyakoribb nemi úton terjedő kórokozója. A daganatkeltő (onkogén) HPV-típusokkal történő fertőzés tehető felelőssé a méhnyakrákok 99,7%-ának kialakulásáért. A megelőzés-ben döntő szerepe van a szűrésnek, amely a méhnyakrák előfordulását és halálozását bizonyítottan csökkentheti. Jelenleg 16 női HPV-centrum működik országszerte, amelyekben egységes irányelvek alapján végeznek szűrése-ket, tanácsadást és gondozást. Az első központot 2007 márciusában jelen közlemény sz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A single HPV-center (University Clinic) examined 1,155 women (not screening population) and found that 55.5% of patients tested positive for HPV DNAs, with 38.5% having high-risk HPV DNA. The most common HPV type found was type 16 (19.5%), with high prevalence of type 51 and 31 among patients with cytological atypia ( 13 ). A study in 2016 examined the HPV genotypes from 2048 cytology results (not in a screening population) and found an hrHPV positivity of 12.7%, with the most prevalent (ranked in order) being 16-52-51-31-66-58 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single HPV-center (University Clinic) examined 1,155 women (not screening population) and found that 55.5% of patients tested positive for HPV DNAs, with 38.5% having high-risk HPV DNA. The most common HPV type found was type 16 (19.5%), with high prevalence of type 51 and 31 among patients with cytological atypia ( 13 ). A study in 2016 examined the HPV genotypes from 2048 cytology results (not in a screening population) and found an hrHPV positivity of 12.7%, with the most prevalent (ranked in order) being 16-52-51-31-66-58 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our geographically-representative screening population, the most frequent genotypes were similar to those found in some of the earlier studies in Hungary. Genotype 16, 51 and 31 had the highest prevalence in 2011 among patients with cytological atypia ( 13 ). A study in 2016 examined the HPV genotypes from 2048 cytology results (not in a screening population) the most prevalent (ranked in order) being HPV16-52-51-31-66-58 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Célunk egyrészt annak felmérése, hogy mekkora a konkrét jelentősége ennek hazai környezetben, figyelembe véve, hogy a hazai HPV-genotípus-prevalenciáról szóló tanulmányok [8][9][10][11][12][13] kettő kivételével [12,13] tíz évnél régebbiek, és csak egy [13] országosan reprezentatív, másrészt rávilágítani a felnőtt és a kiskorú célcsoportok kapcsán is egy-egy olyan etikai dilemmára, amely a védőoltás beadása előtti tájékoztatás során felmerülhet, és megválaszolásuk nem magától értetődő. Oltásról lévén szó, a dobozban lévő alkalmazási előiratot a páciens nem feltétlenül látja vagy olvassa el, a tájékoztatás a vényt kiállító, illetve a védőoltást beadó kezelőorvos feladata és felelőssége.…”
Section: Célkitűzésunclassified
“…Worldwide 6.7 per cent of all malignant tumours is due to oncogenic HPV infection [2]. Malignant tumours associated with HPV have a highest incidence on the cervix, there 99.7 per cent of malignant lesions have oncogenic HPV infection in the background [3]. Oncogenic genotypes have been isolated from cancers of the vulva, vagina, penis, anus and oropharyngeal and oesophageal cancers.…”
mentioning
confidence: 99%
“…In Hungary according to the data of the Hungarian Central Statistical Office the incidence of cervix carcinoma is around 1500 cases per year and around 500 patients die annually [3]. Hungary is the leader in incidence and mortality in oropharyngeal cancer in Europe and is second in the world in terms of men [5] .…”
mentioning
confidence: 99%